Sustainable living and urban density: the choices are wide open - Cheshmehzangi, Ali; Butters, Chris (Elsevier, 2016)
Rapid urbanization, especially in developing countries, means that the worldwide tradition of living in low-rise housing is giving way to life in urban apartments. This implies huge environmental and sociocultural changes. For sustainability, dense cities offer some advantages, including efficient land use and transport systems. But there are also many possible negatives of such urbanization, and particularly for lower income groups. A widespread model is high-rise urban “superblocks”. The reasoning is often said to be the need to house many people in very compact cities. This argument is not strictly true. Equally high population densities can be achieved in several ways, including quite low-rise, with equal energy efficiency as well as environmental and social qualities. We explore these choices and assess options for sustainable living in future urban residential areas. Life cycle analysis is often applied to individual buildings but less often to urban development seen as a whole. We suggest some important “new” considerations need to be taken into account in deciding which urban forms to choose. In particular, high-rise as compared to low-dense options have implications as regards embodied energy, recurrent costs, flexibility and post use, which have to date been little discussed in the research literature.